Effect of calcifediol supplementation on renin‐angiotensin‐aldosterone system mediators in dogs with chronic kidney disease. (13th August 2022) - Miller, Matthew; Quimby, Jessica; Langston, Catherine; Ames, Marisa; Parker, Valerie J.
Abstract: Background: Chronic kidney disease (CKD) leads to low serum concentrations of vitamin D metabolites. Thus, hypovitaminosis D associated with CKD might contribute to disease progression via increased concentration of renin angiotensin aldosterone system (RAAS) mediators. Objectives: To evaluate whether supplementation with calcifediol affects equilibrium concentrations of selected mediators of the RAAS. We hypothesized that vitamin D supplementation will decrease concentration of circulating RAAS mediators in dogs with CKD. Animals: Six client‐owned adult dogs with IRIS Stage 2 and 3 CKD. Methods: Prospective study. Serum 25‐hydroxyvitamin D (25[OH]D), 1, 25‐dihydroxyvitamin D (1, 25[OH]2 D), 24, 25‐dihydroxyvitamin D (24, 25[OH]2 D), RAAS mediators (angiotensin I/II/III/IV/1‐5/1‐7, and aldosterone), and surrogate angiotensin converting enzyme (ACE) activity (calculated by the ratio of angiotensin II to angiotensin I) were evaluated at baseline, after 3 months of calcifediol supplementation, and 2 months after discontinuing administration of supplement. Results: All serum vitamin D metabolite concentrations increased significantly by month 3 ( P  < .001): 25(OH)D (median 250 ng/mL; range, 204‐310), compared to baseline (median 43.2 ng/mL; range, 33.8‐58.3 ng/mL); 1, 25(OH)2 D (median 66.1 pg/mL; range, 57.3‐88.1 pg/mL) compared to baseline (median 35.2 pg/mL; range, 29.3‐56.7 pg/mL); 24, 25(OH)2 D (median 68.4 ng/mL; range, 22.1‐142.0 ng/mL) compared to baseline (median 14.4 ng/mL; range, 9.0‐21.3 ng/mL). Calculated ACE activity was significantly lower at month 3 (median 0.5; range, 0.4‐1.0) compared to baseline (median 0.7; range, 0.6‐1.3; P  = .01). There were no significant differences in any of the evaluated RAAS variables at any other time‐point. Conclusions and Clinical Importance: Short‐term calcifediol supplementation in this small group of CKD dogs appeared to decrease ACE activity.